Pregnant and Postpartum Women Requiring Intensive Care Treatment for COVID-19—First Data from the CRONOS-Registry - Sitter, Magdalena; Pecks, Ulrich; Rüdiger, Mario; Friedrich, Sabine; Malfertheiner, Sara Fill; Hein, Alexander; Königbauer, Josefine T.; Becke-Jakob, Karin; Zöllkau, Janine; Ramsauer, Babett; Rathberger, Katharina; Pontones, Constanza; et al. (Journal of Clinical Medicine, 2022)
(1) Background: Data on coronavirus 2 infection during pregnancy vary. We aimed to describe maternal characteristics and clinical presentation of SARS-CoV-2 positive women requiring intensive care treatment for COVID-19 during pregnancy and postpartum period based on data of a comprehensive German surveillance system in obstetric patients. (2) Methods: Data from COVID-19 Related Obstetric and Neonatal Outcome Study (CRONOS), a prospective multicenter registry for SARS-CoV-2 positive pregnant women, was analyzed with respect to ICU treatment. All women requiring intensive care treatment for COVID-19 were included and compared regarding maternal characteristics, course of disease, as well as maternal and neonatal outcomes. (3) Results: Of 2650 cases in CRONOS, 101 women (4%) had a documented ICU stay. Median maternal age was 33 (IQR, 30–36) years. COVID-19 was diagnosed at a median gestational age of 33 (IQR, 28–35) weeks. As the most invasive form of COVID-19 treatment interventions, patients received either continuous monitoring of vital signs without further treatment requirement (n = 6), insufflation of oxygen (n = 30), non-invasive ventilation (n = 22), invasive ventilation (n = 28), or escalation to extracorporeal membrane oxygenation (n = 15). No significant clinical differences were identified between patients receiving different forms of ventilatory support for COVID-19. Prevalence of preterm delivery was significantly higher in women receiving invasive respiratory treatments. Four women died of COVID-19 and six fetuses were stillborn. (4) Conclusions: Our cohort shows that progression of COVID-19 is rare in pregnant and postpartum women treated in the ICU. Preterm birth rate is high and COVID-19 requiring respiratory support increases the risk of poor maternal and neonatal outcome.
CRIS-Team Scopus Importer:2022-02-04
Keywords: ARDS; COVID-19; Maternal critical care; Obstetrics; Pregnancy; SARS-CoV-2